(untitled) (Cadernos de Sociomuseologia, 2023)
Since the 1990s, sustainability practices have been proposed in international documents that point to guidelines for sustainable development, the most recent example being the 2030 agenda. This article seeks to present, based on the proposal to create the organic museum Salinas and Mangroves in the municipality of Chaval-Ce, the contributions that the creation of a museum can promote for local sustainable development. Following the thinking of social museology, in an inclusive and collaborative way, the community is invited to think about its place and define which cultural assets represent the collectivity and speak about the territory, so that, from the creation of the museum, they can develop the paths they wish to follow to make the city sustainable. The museum will be the he between the memories of the place (past) and the sustainability practices (future) that will be adopted through the construction of itineraries of cultural and environmental experience in the territory, thinking the museological practice integrated with responsible tourism and social management. The present discussion has a descriptive character, as it seeks to describe a phenomenon or a situation in detail, observing its characteristics, values and culture, as for the technical procedures, bibliographic research was used and the field research began. Keywords: Social Museology; Participatory Inventory; Sustainability; Environmental rationality; Responsible tourism.